RELATIONSHIP BETWEEN KNOWLEDGE ABOUT COVID-19 WITH ATTITUDE TO PREVENTING THE SPREAD OF COVID-19 IN STUDENTS OF POLYTECHNIC MIDWIFE STUDIES HOPE TOGETHER IN TEGAL CITY - Ulfatul Latifah; Seventina Nurul Hidayah; Desy Adzkiyatun Nisa (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2022)
Indonesia is a developing country with various types of problems, one of the main problems in Indonesia is health problems which for some time are difficult to control, coupled with the corona virus pandemic (covid-19). The government has made various efforts to decide to prevent the spread of COVID-19 such as imposing Large-Scale Social Restrictions (PSBB), implementing government policies such as Restrictions on Community Activities (PKM) etc which were implemented in several regions in Indonesia. To ensure the success of government programs, community compliance with prevention efforts is very important, which is largely influenced by knowledge and attitudes towards COVID-19, if someone has good knowledge, a positive attitude will be formed and will eventually adopt good practices. . This type of research is analytic, using an observational research design with a cross sectional approach. The purpose of this study was to determine the relationship between knowledge about Covid-19 and attitudes about preventing the spread of COVID-19. The population in this study were 43 students of Midwifery Polytechnic Harapan Bersama Tegal using total sampling technique. Test the analysis using the chi-square analysis test. The results of this study indicate that the respondent's knowledge is sufficient but produces a good attitude, the results of the analysis test show that there is a relationship between knowledge and attitude. It is hoped that students can increase their knowledge as an understanding of COVID-19 and preventing the spread of COVID-19. Keyword: knowledge, attitude, COVID-19